Monsoon-Driven Dispersal of River-Sourced Floating Marine Debris in Tropical Semi-Enclosed Waters: A Case Study in the Gulf of Thailand - Kittipong Phattananuruch; Tanuspong Pokavanich (Journal of Marine Science and Engineering)
Marine debris (MD) causes significant threats to marine ecosystems. However, limited research addresses its transport of MD in tropical shallow semi-enclosed seas. This study applied a validated 3D hydrodynamic model and a particle tracking model to simulate the seasonal distribution of floating marine debris (FMD) originating from major river mouths in the vicinity of the Gulf of Thailand (GoT). The aim was to examine seasonal distribution patterns and variations influenced by sea surface circulation. Simulated particles were released every six hours from 12 river mouths and tracked over three years. Results revealed that seasonal currents drive the distribution of debris between the eastern and western regions, as well as its export and import across the gulf. The upper Gulf of Thailand (UGoT) exhibited the highest concentration of debris, with around 50% of the total released particles ending up onshore across the GoT, varying seasonally. An analysis showed that 74% of the debris released within the gulf remains there. Additionally, the GoT receives approximately 10% of the debris from rivers located outside its boundaries. Findings from this study suggest that the GoT, as an example of a tropical semi-enclosed sea, functions as both a sink and a source for FMD. These results could support the development of strategic seasonal cleanup frameworks, optimizing efforts during peak debris accumulation periods to enhance management efficiency. In addition, the mapping of debris distribution provides critical data for assessing and mitigating marine environmental impacts in the GoT.